Relations between tacts and mands during the acquisition (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
The present study investigated the functional relations between the verbal operants, tact and mand, since the data in the literature is inconclusive. Relations were verified between the verbal operants “Let” and “Zut,” arbitrarily related to the positions, left and right, each with a function either of tact or mand. It was verified the occurrence of responses of mand after the direct training of tact´s responses, from the procedure of multiple training. The subjects were six children between two years and five months and four years and one month, who attended school, in which the study was conducted. Five of six participants emitted not-trained mand responses after the tact training, that is, they presented functional dependence. This result was related to some variables facilitators, such as the procedure of multiple training, the requirement of the verbal community which children were exposed to, the age of the subjects, among others.